2014
DOI: 10.1136/bmjopen-2014-005055
|View full text |Cite
|
Sign up to set email alerts
|

The role of hospital managers in quality and patient safety: a systematic review

Abstract: ObjectivesTo review the empirical literature to identify the activities, time spent and engagement of hospital managers in quality of care.DesignA systematic review of the literature.MethodsA search was carried out on the databases MEDLINE, PSYCHINFO, EMBASE, HMIC. The search strategy covered three facets: management, quality of care and the hospital setting comprising medical subject headings and key terms. Reviewers screened 15 447 titles/abstracts and 423 full texts were checked against inclusion criteria. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
187
0
11

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 202 publications
(203 citation statements)
references
References 56 publications
5
187
0
11
Order By: Relevance
“…[1][2][3][4][5][14][15][16] Our findings contribute to this literature by providing novel evidence on how board and management practices interact with each other and their relationship with quality. We found that several structural features of hospitals, such as teaching hospital status, were related to better management scores.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…[1][2][3][4][5][14][15][16] Our findings contribute to this literature by providing novel evidence on how board and management practices interact with each other and their relationship with quality. We found that several structural features of hospitals, such as teaching hospital status, were related to better management scores.…”
Section: Discussionmentioning
confidence: 68%
“…Less is known about how two critical elements, leadership and management, influence the delivery of high-quality care and how those effects might be empirically verified. 1 Several previous studies have shown an association between hospital board practices and quality of care. [2][3][4][5] Although these studies have been helpful, they have not been able to clearly delineate which specific activities of the boards affect quality of care and how they relate to hospital managers' activities.…”
mentioning
confidence: 99%
“…The importance of leadership is underlined by earlier results on effective quality management systems and governance. [1,9,23,29] Our findings also point to the need for creating and sustaining a culture in which employees perceive participation in auditing as being part of their medical or nursing profession rather than a mandatory element of their work used for administrative and blaming purposes. We found that the emphasis on an audit as a learning opportunity might be a way to steer away from the audit as a "tick-box" activity, which is in line with literature on other types of audits.…”
Section: Discussionmentioning
confidence: 91%
“…[5][6][7][8] There are several sources from which hospital boards can gather quality and safety information, for example safety walk-arounds, patient safety indicators, incident reports, infection rates, patient satisfaction surveys, risk registers and adverse events meetings. [9,10] In almost every Dutch hospital, boards use information deriving from internal audits. [11] The Dutch internal audit system is an "objective assurance and consulting system for detecting patients' risks of adverse events early, and it should encourage the continuous improvement of patient safety".…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, 14.1% of employees have said that senior managers do not have clear understanding and image of risks related to patient care, and 15.8% believed that there is no appropriate communication flow in the hospital's chain of command on the topic of safety [11]. In the healthcare sector, there are clear evidences of the effect of managers on safety at workplace, but there are not enough articles and research on their attitudes and efforts to increase risk and safety management [12]. Therefore, this research has been conducted with the aim of assessing the risk management category and its status in hospital from the perspective of senior managers in Urmia hospitals considering the existing scientific gap and the importance of the issue for the health system and society.…”
Section: Introductionmentioning
confidence: 99%